2021
DOI: 10.1002/cmdc.202100483
|View full text |Cite
|
Sign up to set email alerts
|

Bithiazole Inhibitors of Phosphatidylinositol 4‐Kinase (PI4KIIIβ) as Broad‐Spectrum Antivirals Blocking the Replication of SARS‐CoV‐2, Zika Virus, and Human Rhinoviruses

Abstract: Over half a century since the description of the first antiviral drug, “old” re‐emerging viruses and “new” emerging viruses still represent a serious threat to global health. Their high mutation rate and rapid selection of resistance toward common antiviral drugs, together with the increasing number of co‐infections, make the war against viruses quite challenging. Herein we report a host‐targeted approach, based on the inhibition of the lipid kinase PI4KIIIβ, as a promising strategy for inhibiting the replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Since compound 21 showed interesting antiviral properties against SARS‐CoV‐2 (see Table 1), we decided to exploit the OH moiety on the N9‐chain to conjugate this molecule with another class of BSAAs previously developed by our group to evaluate the possibility of a synergic effect. Compounds 22 [23] and 24 , [28] recently reported by us as promising inhibitors of SARS‐CoV‐2 and other viruses, could be easily linked to compound 21 using two different synthetic approaches (Scheme 5): 1) bithiazole antiviral 22 was activated as imidazolide by reaction with CDI and then coupled with 21 to give the desired conjugate molecule 23 , characterized by an hydrolyzable carbonate linker; 2) bithiazole antiviral 24 was converted to the corresponding acyl chloride and then reacted with 21 to afford the desired conjugate molecule 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Since compound 21 showed interesting antiviral properties against SARS‐CoV‐2 (see Table 1), we decided to exploit the OH moiety on the N9‐chain to conjugate this molecule with another class of BSAAs previously developed by our group to evaluate the possibility of a synergic effect. Compounds 22 [23] and 24 , [28] recently reported by us as promising inhibitors of SARS‐CoV‐2 and other viruses, could be easily linked to compound 21 using two different synthetic approaches (Scheme 5): 1) bithiazole antiviral 22 was activated as imidazolide by reaction with CDI and then coupled with 21 to give the desired conjugate molecule 23 , characterized by an hydrolyzable carbonate linker; 2) bithiazole antiviral 24 was converted to the corresponding acyl chloride and then reacted with 21 to afford the desired conjugate molecule 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies reported the identification of potent PI4KIIIβ inhibitors with broad‐spectrum antiviral (BSA) activity (e. g. MR105) but also novel antiviral‐correctors (e. g. MR250) able to restore ΔF508‐CFTR biogenesis/function and inhibiting the replication of multiple picornaviruses representative of all major groups: enterovirus group A (enterovirus 71 strain BrCr), group B (Coxsackievirus B3), group C (poliovirus 1 strain Sabin), group D (enterovirus 68 strain CU70), rhinovirus group A (hRV14) and rhinovirus group B (hRV02) [25–27] . On the other hand, the known bithiazole‐based CFTR corrector (Corr4a, Figure 1) did not display any effect on the PI4KIIIβ kinase and no antiviral activity on the above mentioned viruses, thus confirming that the structure of this bithiazole scaffold can be finely tuned to reach the desired polypharmacological effect.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the antiviral activity of candidate compounds against SARS-CoV-2, a DYRA, based on the infection of cells in the presence of serial drug dilutions, was performed as previously described, with minor modifications [ 25 ]. Briefly, 25,000 Calu-3, pre-seeded in the 96-well plates, were treated with serial dilutions of each tested compound, and incubated for 30′ at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Starting from these considerations, we have prepared a small but representative panel of metal compounds of medicinal interest with the aim of evaluating their efficacy in vitro against SARS-CoV-2. The panel compounds were screened for their anti-SARS-CoV-2 properties according to an experimental protocol established at the University of Siena [ 25 ]. As the screening highlighted the favorable anti-SARS-CoV-2 properties of three panel compounds, we decided to perform a computational study to better understand the likely origins of their antiviral properties.…”
Section: Introductionmentioning
confidence: 99%